4(x+4)+14=-2x

Simple and best practice solution for 4(x+4)+14=-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+4)+14=-2x equation:


Simplifying
4(x + 4) + 14 = -2x

Reorder the terms:
4(4 + x) + 14 = -2x
(4 * 4 + x * 4) + 14 = -2x
(16 + 4x) + 14 = -2x

Reorder the terms:
16 + 14 + 4x = -2x

Combine like terms: 16 + 14 = 30
30 + 4x = -2x

Solving
30 + 4x = -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
30 + 4x + 2x = -2x + 2x

Combine like terms: 4x + 2x = 6x
30 + 6x = -2x + 2x

Combine like terms: -2x + 2x = 0
30 + 6x = 0

Add '-30' to each side of the equation.
30 + -30 + 6x = 0 + -30

Combine like terms: 30 + -30 = 0
0 + 6x = 0 + -30
6x = 0 + -30

Combine like terms: 0 + -30 = -30
6x = -30

Divide each side by '6'.
x = -5

Simplifying
x = -5

See similar equations:

| 0.5x^2-3x=0 | | -9x+27=9y | | 10+10=100x | | (0-1)3x-y=1 | | 4a+7b=10 | | 0=4x^2+9x+5 | | 9+6=24x | | 5+4=8x | | 11=2+3y | | (8+w)(3w-4)=0 | | -3q=91.5 | | 3q=91.5 | | x-63=-9x+7 | | -14.1p+18.33=-16.12-19.4p | | 0=-8x^2+7x+6 | | x^3-19x^2+90x=56 | | -4/5m=5/7 | | x^3-19x^2+90x-56=0 | | 3(3.99)+1(x)=5x-.11 | | 5r-9=4 | | -14.08-2.4r=-1.2r-3.95-1.85 | | -20t=80 | | 2u+3+4u-18=114 | | x-62=57-6x | | -3(5x-2)=16x-5 | | 148+128+2x+(2x+40)=540 | | x-60=-10x+6 | | 132+x=22 | | 5r-11=4 | | f(x)=8x^2+7x+6 | | -30=q-1 | | -167+4x=-3x+43 |

Equations solver categories